The synthesis and characterization of ZnS nanoparticles from zinc-based thiourea derivative complexes for potential use in photocatalysis - Lethobane, Manthako Hycinth (My University, 2017)
Nanotechnology has been instrumental in finding strategies of combating some of the world’s grand challenges. Water scarcity and the growing industrialization have made it an imperative to find ways of cleaning water. Photocatalysis is a promising method for water purification personified by the use of solar energy as well as nanomaterials with tailored properties. Colloidal synthesis has made it possible to synthesize new materials with tailored properties, in particular the single-source precursor method has been found to be a useful method in synthesizing nanomaterials with high purity. In the synthesis of metal chalcogenides, the single-source precursor method has an advantage of the precursor having the desired metal-chalcogenide bond hence eliminating the possible formation of side products particularly metal oxides. Herein, acylthiourea (ATU) and thiourea (TU) zinc complexes were used as precursors for the synthesis of ZnS nanoparticles. Bis(N,N-diethyl-N’-benzoylthiourea)Zn(II) [Zn(ATU)2] and bis(diaminomethylthio)Zn(II) chloride [Zn(TU)2Cl2] complexes were synthesized using a conventional method and characterized with elemental analysis, 1H NMR , 2D NMR, COSY, FTIR, mass spectrometry and X-Ray crystallography. The resultant precursors, Zn(ATU)2 and Zn(TU)2Cl2 complexes were then thermolyzed to yield ZnS nanocrystals and characterized fully. Reaction parameters that included the synthetic time, temperature, concentration and capping agents were optimized for each single-source precursor in an attempt to control the nanoparticles yielded hence their properties. Time and temperature studies generally demonstrated the most pronounced effect and with an increase, they showed increasing particle sizes through the Ostwald ripening effect. Also visible from the TEM was that the temperature had an effect on the morphology of the nanoparticles. Increasing the precursor concentration resulted in the agglomeration of nanoparticles, while using different capping agents yielded similar nanoparticles with different degrees of agglomeration. Evident from the results the ATU precursor behaved similar to the TU precursor and generally the particles obtained from the two precursors regardless of the reaction condition were very small. Preliminary investigations into the use of the synthesized nanoparticles obtained from the two precursors revealed potential in photocatalytic degradation of Rhodamine B (RhB) dye in water. While smaller particles were obtained from the synthesized nanoparticles, the degradation efficiencies were lower than the commercial ZnO and TiO2. This is due to the presence of the long-chained capping agents on the synthesized particles blocking the interaction of the core ZnS and the light.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand in partial fulfilment of the requirement for the degree Master of Science (M.Sc.) in Chemistry. Johannesburg, 31 October 2017.
Keywords: Water--Purification--Photocatalysis; Photocatalysis; Nanotechnology